Design controls for the medical device industry - Teixeira, Marie B., 1965- (Taylor & Francis, 2013)
"Design control is a key element of a company's quality management system and is mandated by the U.S. FDA's Quality System Regulation under article 820.30 for most medical devices. Medical device companies wishing to comply with ISO 13485 to meet international requirements are also subject to design control requirements. This second edition of a bestselling book expands and updates all chapters with detail on current design control requirements, more examples, and further explanation and clarification of the requirements. The book also addresses device risk and classification, and covers risk management in its own chapter. Appendices have also been revised"--Provided by publisher